Metodologías innovadoras y su influencia en la enseñanza de los docentes de la carrera de Contabilidad y Auditoría en la Universidad Nacional de Loja - Cabrera Rivera, Paola Lizbeth (2024)
Today's world is characterized by rapid technological advances and constant changes in various fields, thus higher education faces the challenge of preparing students for a dynamic and globalized work environment; Therefore, this work analyzes the influence of innovative methodologies in the teaching process of teachers of the Accounting and Auditing career at the National University of Loja, who mention that they have observed improvements in student learning as result of the implementation of innovative methodologies, ten teachers indicate that they allow active participation and greater interaction between teachers and students with 34.48%; seven teachers consider that there is greater attention and motivation in the process with 24.14%; six teachers, that is, 20.68%, consider that there is better understanding and autonomous work in the students; while for two teachers it allows them to relate theory to practice, as well as generate better reasoning and judgment in students; for a teacher, more skills and abilities are developed; however, a teacher with 3.45% considers that no improvement is observed. As a result, innovative methodologies contribute significantly to the teaching-learning process and innovative methodological resources are proposed that contribute to optimizing the quality of education. So, the research aligns with the Sustainable Development Goals, specifically with "Ensure inclusive, equitable and quality education and promote lifelong learning opportunities for all"; Likewise, it is linked to institutional priorities, adjusting to the line of research called Educational Innovation, of the master's program, achieving a focus on the identification and socialization of innovative methodologies, generating a positive impact on the teaching process and training of future professionals.